An Analysis of Sunday School Teachers Understanding of Children with Special Needs - Siten, Anggita Deodora; Merdiasi, Danella; Kinasih, Ditha Maharani (Universitas Syiah Kuala, 2025)
This research is to describe Sunday school teachers' understanding of the conditions of children with special needs at the GKE Pahandut Palangka Raya Hilir Resort. The research method used is qualitative research which aims to obtain an in-depth understanding which emphasizes understanding the subjective elements of the individual himself regarding the phenomenon being studied and is considered appropriate in answering the research problem. There were 4 subjects in this research, including Sunday school teachers for children with special needs at the GKE Pahandut Palangka Raya Hilir Resort. The results of this research generally show that teachers have a good level of understanding regarding children with special needs. This level of understanding does not mean that teachers fully understand the needs of children, but here the teachers have knowledge about children with special needs, although in its application the teachers still experience difficulties several times. Meanwhile, teachers' understanding of the needs of children with special needs is in the form of extrapolation understanding. Some teachers are quite capable of distinguishing the specificities experienced by children with special needs. Meanwhile, the factors that influence Sunday School teachers' understanding of the condition of Children with Special Needs at Pahandut Resort Palangka Raya Hilir include internal factors, namely those related to psychological (emotional) factors and external factors that influence Sunday School teachers' understanding, namely experience and work.